Peningkatan Ekonomi Petambak Garam Melalui Penerapan Teknologi Geomembran di Desa Sondosia Kecamatan Bolo Kabupaten Bima - M Yusuf; Muhammad Nursan; Anwar Anwar; Fadli Fadli; Aeko Fria Utama FR; Rifani Nur Sindy Setiawan; Anna Apriana Hidayanti; Eka Nurminda Dewi Mandalika; Dudi Septiadi (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2023)
The purpose of this service activity is to: (1) improve the knowledge and skills of the farmers relating to: (a) technical aspects and socio-economic aspects of geomembrane technology; (b) Management of salt farming with the development of geomembrane technology (2) knowing the response of salt farmers regarding geomembrane technology (3) establishing relationships between universities and the community. Implementation of activities carried out using the andragogy method through counseling and demonstrations to the target group. The results of the activity show that: (1) this activity has been able to increase the knowledge and skills of salt farmers especially relating to: (a) technical aspects and socioeconomic aspects especially related to improving the community's economy, especially salt farmers through the development of geomembrane technology; (b) Management of salt farming using geomembrane technology shows good results, is healthy and environmentally friendly; (c) group management ability in efforts to take advantage of existing potential is good; (2) The response of salt farmers to extension activities is quite high; (3) This activity has increased communication between tertiary institutions, especially UNRAM, and the community.